LEARNING ENGLISH READING SKILL THROUGH E-LEARNING - Baiatun Nisa (Wanastra: Jurnal Bahasa dan Sastra, 2017)
This study aims at deep-portraying the learning of reading skill at Universitas Terbuka (UT, literally Open University) Indonesia. The research was conducted from March 2014 to February 2015. The approach used in this study is a qualitative approach conducted with ethnographic methods by adopting the method of Spradley. The data collecting techniques being used were observation, interview, and document analysis. Data is analyzed by using techniques such as domain, taxonomy, component, and theme analysis. The result of the analysis shows that the learning system implemented at UT is through the use of the Internet known as e-learning or online tutorial is appropriate and involve many means to improve reading skills such as the presence of additional materials (initiation), online discussions, and digital library. The cultural finding which is continuously occuring within the learning process is the emerging new roles of teacher in e-learning based on classes. These roles include: (1) mastering the ICT and having the ability to handle technical problems on the technology; (2) having the ability to interact with students in written form; (3) becoming a motivator; and (3) giving written feedback to students.